Poliovirus immunity in newly resettled adult refugees in Idaho, United States of America. Issue 26 (12th June 2015) - Roscoe, Clay; Gilles, Ryan; Reed, Alex J.; Messerschmidt, Matt; Kinney, Rebecca
Abstract Background In the United States, vaccines have eliminated wild poliovirus (WPV) infection, though resettling refugees may lack immunity and importation of WPV remains a concern. Methods A cross-sectional survey was performed to determine the prevalence of poliovirus immunity in adult refugees resettling in Boise, Idaho, U.S.A.; immunity was evaluated using two definitions: serotypes 1, 2 and 3 positive, or serotypes 1 and 3 positive. Results This survey evaluated 795 adult refugees between August 2010 and November 2012. Poliovirus immunity in adults >18 years was 55.3% for serotypes 1, 2 and 3 combined, and 60% for serotypes 1 and 3 only. Conclusion This study demonstrated a WPV immunity rate of <60% in a recently resettled adult refugee population in the United States, reinforcing the need to ensure poliovirus immunity in all newly arrived adult refugees, either by expanding pre-departure immunization or by screening for immunity at resettlement and vaccinating when indicated.